(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Instrumental methods of investigation are used to assess the anatomo-morphological and functional status of the kidney and urinary tract. These include radiologic and radionuclide methods, ultrasound and kidney biopsy.